Real-Life Outcomes of Bosutinib in Patients with Chronic Myeloid Leukemia: A Multicenter Nationwide Study from Turkey - Guven, Serkan; Ozmen, Deniz; Catma, Yunus; Koca, Tuba Gullu; Kirkizlar, Onur; Seker, Omer; Eskazan, Ahmet Emre (Elsevier, 2024)
[Abstract Not Available]
66th Annual Meeting of the American-Society-of-Hematology (ASH) -- DEC 06-09, 2025 -- Orlando, FL